A quantitative analysis of rotary, ultrasonic and manual techniques to treat proximally flattened root canals - Fabiana Soares Grecca; Roberto Brandão Garcia; Clóvis Monteiro Bramante; Ivaldo Gomes de Moraes; Norberti Bernardineli (University of São Paulo, 2007)
OBJECTIVE: The efficiency of rotary, manual and ultrasonic root canal instrumentation techniques was investigated in proximally flattened root canals. MATERIAL AND METHODS: Forty human mandibular left and right central incisors, lateral incisors and premolars were used. The pulp tissue was removed and the root canals were filled with red die. Teeth were instrumented using three techniques: (i) K3 and ProTaper rotary systems; (ii) ultrasonic crown-down technique; and (iii) progressive manual technique. Roots were bisected longitudinally in a buccolingual direction. The instrumented canal walls were digitally captured and the images obtained were analyzed using the Sigma Scan software. Canal walls were evaluated for total canal wall area versus non-instrumented area on which dye remained. RESULTS: No statistically significant difference was found between the instrumentation techniques studied (p<0.05). CONCLUSION: The findings of this study showed that no instrumentation technique was 100% efficient to remove the dye.